THE CURRENT STATE OF THE COMMUNITY CENTERS IN RESIDENTIAL AREAS OF KYIV - Savchenko, Roman (Theory and practice of design, 2025)
The article defines the current state of public centers in the residential districts of Kyiv within the broader context of research aimed at identifying the principles of environmental comfort in public centers of residential areas. The spatial organization, functional composition, urban planning, and social roles of these centers within the framework of the contemporary Ukrainian city are analyzed. Purpose. To determine the current state of public centers in the residential districts of Kyiv. Methodology. Spatial analysis, graph-analytical method, typological and structural analysis, field surveys, and comparative method were applied. The study is based on materials from field observations and photographic documentation, cartographic data, spatial-functional schemes, existing urban planning documents, standards, and scholarly sources in the research field. Results. The article establishes the current state of public centers in the residential districts of Kyiv. The analysis revealed that most public centers possess a structure segmented by transport infrastructure, which reduces the overall quality and comfort level of the center’s environment. A deficit of recreational and cultural facilities was identified, along with a significant imbalance in functional composition favoring commercial components. The centers display low levels of inclusivity and safety. Notable trends include: a shift of activity centers toward transport hubs and the growing prominence of monofunctional facilities. Scientific novelty. The article updates data on the present state and formation trends of public centers in Kyiv’s residential districts, specifying the comfort level of their environment in spatial, functional, and social terms. Practical relevance. The findings may be used in the development of reconstruction projects for public centers in Kyiv residential districts and in the update of urban planning documentation.